OC-067 Different Mechanisms of Disease in Subtypes of Irritable Bowel Syndrome as Demonstrated by MRI. (17th August 2016) - Lam, C; Chaddock, G; Marciani, L; Costigan, C; Cox, E; Hoad, C; Pritchard, S; Gowland, P; Spiller, R
Abstract : Introduction: The study of irritable bowel syndrome (IBS) has been hampered by the absence of biomarkers to accurately categorise subgroups of this heterogeneous condition. Our aim was to assess gut transit, small bowel water content and colonic regional volumes of different clinically defined IBS subtypes both fasted and post-prandially using MRI scans. Methods: 91 subjects were recruited (34 healthy volunteers (HV), 30 IBS with diarrhoea (IBS-D), 16 IBS with constipation (IBS-C) and 11 IBS with mixed bowel habit (IBS-M). Subjects underwent MRI scans every 45 min on the study day. Whole gut transit times (WGTT), small bowel water content (SBWC) and regional colonic volumes were assessed as previously described 1, 2, 3 . Abdominal symptoms were scored using visual analogue score questionnaires after each set of MRI scans. Breakfast was given before t = 0 and lunch after t = 360 min. Postprandial assessment is timed between t = 0 to t = 360 min. Results: (See Table 1 ). Fasting and postprandial SBWC area under the curve (AUC) in IBS-D and IBS-M were significantly less than HV, p = 0.02 & p < 0.01 (1 way ANOVA) respectively. The fasting transverse colon volume in IBS-C was significantly larger compared to HV, IBS-D and IBS-M p = 0.02 (Kruskal-Wallis). The AUC postprandial total colonic volume for IBS-C was significantly larger than HV and IBS-D, p = 0.03(Kruskal-Wallis). The WGTT for IBS-C was significantly longer than HV and IBS-D, p = 0.02(Kruskal-Wallis). There was significant correlation between bloating score (VAS 0–10 cm) and transverse colon volume after lunch (t = 405 min) with spearman r = 0.21, p = 0.04. Conclusion: The constricted small bowel in IBS-D & IBS-M and the dilated transverse colon in IBS-C point to significant differences in underlying mechanisms of disease in these IBS subtypes. References: 1 Chaddock G, et al . Neurogastroenterol Motil 2014;26 :205–214. 2 Pritchard SE, et al . Neurogastroenterol Motil 2014;26 :124–30. 3 Hoad CL, et al . Phys Med Biol 2007;52 :6909–22. Disclosure of Interest: C. Lam: None Declared, G. Chaddock: None Declared, L. Marciani: None Declared, C. Costigan: None Declared, E. Cox: None Declared, C. Hoad: None Declared, S. Pritchard: None Declared, P. Gowland: None Declared, R. Spiller Grant/research support from: Lessafre and Ironwood, Consultant for: Almirall, Yuhan Corporation, Ibsen and Danone, Speaker bureau with: Menarini